Pilates for abs [videorecording (DVD)]. - Smith, Kathy; Lewis, Madeleine (Sony Music Entertainment, 2001)
Fitness maven Kathy Smith employs the insights of Pilates training in this workout, which is geared to give users a flat stomach and the graceful bearing of a dancer while building core strength for sports and daily activities.